Heart On Fire: An Incidentally Found Case of Native Valve Infective Endocarditis Due to Escherichia coli - Frank, Landon; Bannon, Mark; Marak, Creticus; White, Hunter; Casas, Jack; Kaushik, Prashant (Archives of Clinical and Medical Case Reports, 2024)
Escherichia coli (E. coli) is a common bacterium in the intestinal flora. It can cause severe extraintestinal infections, including infective endocarditis (IE), a bacterial infection of the heart's endocardium and valves. Historically associated with rheumatic heart disease, IE now affects a broader range of patients, including those with prosthetic valves, congenital heart disease, and implantable electronic cardiac devices. While Staphylococcus and Streptococcus species are the leading causes of IE, E. coli IE is rare and presents unique clinical challenges. Here, we report a rare case of E. coli IE, highlighting its unusual presentation and management considerations.